2018
DOI: 10.1017/s1049023x1800078x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patients Presenting with Alcohol and/or Drug Intoxication on In-Event Health Care Services at Mass-Gathering Events: An Integrative Literature Review

Abstract: Substance use and/or intoxication can place a strain on in-event medical services at mass-gathering events. Of the various types of mass-gathering events, music festivals appear to be the most affected by substance use and intoxication. BullockM, RanseJ, HuttonA. Impact of patients presenting with alcohol and/or drug intoxication on in-event health care services at mass-gathering events: an integrative literature review. Prehosp Disaster Med. 2018;33(5):539-542.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The higher number and proportion of young adults arriving to the ED by ambulance during Schoolies week is clinically important as it indicates potential impact on prehospital and in‐ED resources. The presence of higher qualified medical staff (rather than first responder volunteers) has been noted elsewhere to impact (reduce) the transfer to hospital rate . Further research describing the nature of care delivery and diagnoses for young adults arriving to the ED by ambulance during Schoolies week would be helpful in determining staffing, equipment, resources and economic considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The higher number and proportion of young adults arriving to the ED by ambulance during Schoolies week is clinically important as it indicates potential impact on prehospital and in‐ED resources. The presence of higher qualified medical staff (rather than first responder volunteers) has been noted elsewhere to impact (reduce) the transfer to hospital rate . Further research describing the nature of care delivery and diagnoses for young adults arriving to the ED by ambulance during Schoolies week would be helpful in determining staffing, equipment, resources and economic considerations.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The availability of alcohol at sporting MGEs has been repeatedly shown to predispose participants to inadvertent injury and harm resulting in increased PPRs to in-event health services. 9,13,[32][33][34] This review, however, has demonstrated that despite alcohol being available at sporting MGEs, less than ten percent of presentations to in-event health services are as a result of alcohol or drug intoxication. Arbon, Bridgewater, and Smith 34 found that one percent of patient presentations to 201 various Australian MGEs were drug and alcohol related, with just under 12% of those people requiring transport to hospital, yet 99% of drug and alcohol related presentations were at MGEs where alcohol was available.…”
Section: Discussionmentioning
confidence: 99%
“…40 Multiple studies have suggested, however, that the presence of highly skilled health professionals at in-event health services reduces the demand on ambulance services and EDs. 33 Peaks in ED presentations related to drugs and alcohol have been identified in the literature to occur more commonly before and after the sporting MGE. 39,41 Similar to the findings reported by Todkill, et al, 26 a peak in presentations due to illicit drug use was observed immediately after the Sydney 2000 closing ceremony; the majority of whom were transported to hospital by ambulance.…”
Section: Discussionmentioning
confidence: 99%
“…Triage is an essential component of providing unscheduled health services, particularly during disasters 1 and at mass gatherings where marked variability in demand is seen. 2 Triage allows efficient utilization of health care resources, which leads to better matching of demand for and supply of health care resources, including in mass-casualty settings. 3 Triage has been a standard part of delivering emergency medicine for decades, and is widely discussed in the disaster management literature.…”
Section: Introductionmentioning
confidence: 99%